2020
DOI: 10.1186/s13148-020-00827-3
|View full text |Cite
|
Sign up to set email alerts
|

CHD4/NuRD complex regulates complement gene expression and correlates with CD8 T cell infiltration in human hepatocellular carcinoma

Abstract: Backgrounds: The NuRD (Nucleosome Remodeling and Deacetylation) complex is a repressive complex in gene transcription by modulating chromatin accessibility of target genes to transcription factors and RNA polymerase II. Although individual subunits of the complex have been implicated in many other cancer types, the complex's role in human hepatocellular carcinoma (HCC) is not fully understood. More importantly, the NuRD complex has not yet been investigated as a whole in cancers. Methods: We analyzed the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 28 publications
1
49
0
Order By: Relevance
“…Numerous researches and clinical studies have con rmed the signi cance of immune in ltration in solid neoplasms. [26]. Wei et al reported that sperm-associated antigen 5 (SPAG5) was a marker of adverse outcome, and its expression was positively associated with the in ltration of neutrophils, CD8+ T cells, B cells , dendritic and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researches and clinical studies have con rmed the signi cance of immune in ltration in solid neoplasms. [26]. Wei et al reported that sperm-associated antigen 5 (SPAG5) was a marker of adverse outcome, and its expression was positively associated with the in ltration of neutrophils, CD8+ T cells, B cells , dendritic and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…RNA extraction, reverse transcription, and quantitative real‐time PCR were carried out as previously described [20].…”
Section: Methodsmentioning
confidence: 99%
“…TTCTCCGAACGTGTCACGT. Lentivirus preparation was performed as previously described [20]. The lentivirus was then used to infect BT549 cells to knock down C/EBPβ expression followed by selection using puromycin.…”
Section: Cell Culture and Rnaimentioning
confidence: 99%
See 1 more Smart Citation
“…Chromodomain Helicase DNA-binding protein 4 (Chd4) is a chromatin remodeling enzyme that is part of the Nucleosome Remodeling and Deacetylation (NuRD) complex. The NuRD complex is a transcriptional co-repressor that is known to influence chromatin accessibility and enhancer activity 54 , and it has frequently been tied to oncogenesis 55,56,57 . Recently, Goodman et al 28 studied WT and Chd4-knockout (KO) murine cerebellar cells, establishing a relationship between Chd4 and genome architecture in the mammalian brain.…”
Section: Chd4-knockout Versus Wild Type In Murine Cerebellar Granule mentioning
confidence: 99%